Pengaruh Sumber Daya Manusia Terhadap Kinerja Karyawan Di Kap Suparman Bambang Ghanis - Pradhana Jayasukmana; Noor Muhammadi (LPPM-STPI, 2021)
This study aims to determine how much influence human resource planning on employee performance can help companies to improve employee performance. The data used is secondary data from the results of questionnaires to sample employees.The analysis used in this study is a quantitative method test using SPSS Version 20.00 with a significant (?) of 5% and using a simple linear regression statistical model, correlation, and the coefficient of determination (R2), with the influence of human resource planning as the dependent variable . Hypothesis testing with T test shows that the influence variable of human resource planning influences employee performance with t count> t table. This means that employee performance is influenced by the influence variables of human resource planning, the rest is influenced by other variables not mentioned in the hypothesis testing results model, and the two independent variables have a significant effect on employee performance at a significant level of 5%. Based on the analysis, the relationship between the influence of human resource planning and employee performance on KAP Suparman Bambang Ghanis has a strong positive relationship.This can be seen and proved the relationship between the influence of human resource planning and employee performance in KAP Suparman Bambang Ghanis there is a strong positive relationship. This can be seen and proven from the value of Correlation = r = 0.878 (close to 1 relation x to strong Y positive). The results showed that (R square = 77.1%). So, the influence of human resource planning has an influence on employee performance by 77.1% while the remaining 28.9% is explained by other factors outside the variable sentences used in the study. Then the results of the study stated that the count of 8.343 is greater than t table (2.00856), the significance of 0.000 is smaller than 0.05, so Ho is rejected thus the influence of human resource planning (x) has a significant effect on employee performance (Y). Regression coefficient Y = a + bX, the effect of human resource planning (X) is 0, meaning that the employee's performance (Y) is positive 16,853. Regression coefficients influence variables of human resource planning (X) of 0.597, meaning that if the influence of human resource planning increases, employee performance increases, t count of 8.343 is greater than t table (2.00856), the significance of 0.000 is less than 0.05, so Ho is rejected thus the influence of human resource planning (x) has a significant effect on employee performance (Y).